1998
DOI: 10.1103/physrevb.58.r10167
|View full text |Cite
|
Sign up to set email alerts
|

Possibility ofp-wave pairing of composite fermions atν=12

Abstract: We find that for the pure Coulomb repulsion the composite Fermi sea at ν = 1/2 is on the verge of an instability to triplet pairing of composite fermions.It is argued that a transition into the paired state, described by a Pfaffian wave function, may be induced if the short-range part of the interaction is softened by increasing the thickness of the two-dimensional electron system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 30 publications
9
96
0
Order By: Relevance
“…͑51͔͒ using the numerical results of Ref. 68, and we obtained extremely similar results. Stepping back a little from that analysis with the Chern-Simons treatment, one can pretend ignorance of any knowledge of the parameters including the effective mass m ‫ء‬ and the exchange contribution to −1 , and ask what values of them would give good agreement between the values of extracted from experiments.…”
Section: Summary and Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…͑51͔͒ using the numerical results of Ref. 68, and we obtained extremely similar results. Stepping back a little from that analysis with the Chern-Simons treatment, one can pretend ignorance of any knowledge of the parameters including the effective mass m ‫ء‬ and the exchange contribution to −1 , and ask what values of them would give good agreement between the values of extracted from experiments.…”
Section: Summary and Discussionsupporting
confidence: 72%
“…For Eq. ͑51͒, Park et al 68 also reported the ground-state energy for polarized composite Fermi liquid to be very close to the unpolarized one quoted above,…”
Section: ͑44͒mentioning
confidence: 76%
See 2 more Smart Citations
“…In recent years, with the advent of the composite fermion (CF) model [6,7], there has been a renewed interest in the ν = 5/2 state [8][9][10][11][12][13][14][15][16][17][18][19]. Moore and Read (MR) proposed a ground state of p-wave paired CF's [8].…”
mentioning
confidence: 99%